Correlation between Li Plating Behavior and Surface Characteristics of Carbon Matrix toward Stable Li Metal Anodes - Cui, Jiang; Yao, Shanshan; Ihsan‐Ul‐Haq, Muhammad; Wu, Junxiong; Kim, Jang‐Kyo (Advanced energy materials, 2019)
Carbonaceous materials are widely employed to host Li for stable and safe Li metal batteries while relatively little effort is devoted to tailoring the surface properties of carbon to facilitate uniform Li plating. Herein, the correlation between Li plating behavior and the surface characteristics of electrospun porous carbon nanofibers (PCNFs) is systemically elucidated through experiments and theoretical calculations. It is revealed that the neat carbon surface suffers from severe lattice mismatch with Li metal, hindering uniform Li plating. In contrast, open pores created on the PCNF surface serve as active sites for controlled initial nucleation of Li. The introduction of oxygenated functional groups further facilitates the nucleation of Li on PCNFs through the largely reduced nucleation energy barrier. The Li film uniformly deposited on PCNFs enables efficient use of the whole carbon surface, giving rise to enhanced cyclic stability of the electrode. When used as an anode in lithium–sulfur batteries, the modified electrode delivers an excellent energy density of 385 Wh kg−1 after 100 cycles. The fundamental correlation established in this study is universal to all types of carbonaceous materials and sheds new light on the rational design of high‐performance Li metal anodes by controlling the initial Li nucleation. Electrospun porous carbon nanofibers are plated with lithium and the correlation between surface characteristics of the carbon matrix and plating behavior is elucidated. Experiments and theoretical calculations reveal positive contributions of open pores and oxygenated functional groups to uniform Li plating. The Li metal anode delivers an exceptional energy density of 385 Wh kg−1 after 100 cycles in Li–S batteries.